Biomonitoring of firefighting forces: a review on biomarkers of exposure to health-relevant pollutants released from fires. (3rd April 2023) - Barros, Bela; Oliveira, Marta; Morais, Simone
ABSTRACT: Occupational exposure as a firefighter has recently been classified as a carcinogen to humans by International Agency for Research on Cancer (IARC). Biomonitoring has been increasingly used to characterize exposure of firefighting forces to contaminants. However, available data are dispersed and information on the most relevant and promising biomarkers in this context of firefighting is missing. This review presents a comprehensive summary and critical appraisal of existing biomarkers of exposure including volatile organic compounds such as polycyclic aromatic hydrocarbons, several other persistent other organic pollutants as well as heavy metals and metalloids detected in biological fluids of firefighters attending different fire scenarios. Urine was the most characterized matrix, followed by blood. Firefighters exhaled breath and saliva were poorly evaluated. Overall, biological levels of compounds were predominantly increased in firefighters after participation in firefighting activities. Biomonitoring studies combining different biomarkers of exposure and of effect are currently limited but exploratory findings are of high interest. However, biomonitoring still has some unresolved major limitations since reference or recommended values are not yet established for most biomarkers. In addition, half-lives values for most of the biomarkers have thus far not been defined, which significantly hampers the design of studies. These limitations need to be tackled urgently to improve risk assessment and support implementation of better more effective preventive strategies.